The Algorithms and Data Structures course multicomponent complexity and interdisciplinary connections - Korotenko, Gregory; Korotenko, Leonid (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The experience of modern education shows that the trajectory of preparing students is extremely important for their further adaptation in the structure of widespread digitalization, digital transformations and the accumulation of experience with digital platforms of business and production. At the same time, there continue to be reports of a constant (catastrophic) lack of personnel in this area. The basis of the competencies of specialists in the field of computing is the ability to solve algorithmic problems that they have not been encountered before. Therefore, this paper proposes to consider the features of teaching the course Algorithms and Data Structures and possible ways to reduce the level of complexity in its study